ANALISIS PERBEDAAN GENDER DALAM PERKEMBANGAN BAHASA ANAK DI SDN 1 TUKMUDAL - Jelita; Kartika; Nurkholis (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze differences in language skills based on gender at SDN 1 Tukmudal. The method used is qualitative and involves 27 students. Data was obtained through observation and tests that include listening, speaking, reading and writing skills. The results of the observation show that female students are more proficient in using language, especially in terms of vocabulary and fluency. On the other hand, male students tend to use firm and concise language more often. These results are expected to be the basis for designing a learning process that is in accordance with the character of each gender.